Letter (copy) : Help for the workers of Spain - Tewson, Vincent
010-0075-001 Our Ref: HVT/FC/EK/122 17th October, 1936. Miss Betty L. Arne, Women's Section, The Council of Action for Peace and Reconstruction, Horseferry House (Dean Ryle Street), Horseferry Road, S.W.1. Dear Miss Arne, HELP FOR THE WORKERS OF SPAIN FUND Many thanks for your letter of the 16th instant enclosing copy of a Memorandum which has been circulated by your Council to the Press and to 300 key people up and down the country, who are connected with other organisations. Please accept our thanks for your good wishes for the success of the Fund, and in accordance with your request we will let you know of any assistance given to the Fund which can be directly traced to your appeal. Yours sincerely, for Joint Secretary. 292/946/10/80